Akses keadilan dan migrasi global : kisah perempuan Indonesia pekerja domestik di Uni Emirat Arab - Irianto, Sulistyowati; Universitas Indonesia. Pusat Kajian Wanita dan Jender; International Development Research Centre (Canada). (Jakarta : Pusat Kajian Wanita dan Gender, Universitas Indonesia & International Development Research Center, Canada, 2011)
Social problems and legal aspects of Indonesian domestic female workers in United Arab Emirates countries.
Mengandungi rujukan bibliografi (p. 304-313) dan indeks.
Keywords: Women household employees -- United Arab Emirates; Women foreign workers -- United Arab Emirates; Foreign workers, Indonesian -- United Arab Emirates